The Potential use of Anthropometric Parameters to Predict the Anemia Status of Adolescent Girls - Oktaviana, Melda; Dwiriani, Cesilia Meti; Dewi, Mira (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The study assesses the potential use of anthropometric parameters and their optimal cut-off value for predicting the anemia status of adolescent girls. This cross-sectional study analyzed data from 2,184 adolescent girls aged 15‒19 years from West Bandung and Sumedang districts of Indonesia who participated in the Better Investment for Stunting Alleviation Program (BISA). Anemia is defined as a Haemoglobin (Hb) level <12 g/dl and was analyzed by HemoCue® 201+. Anthropometric parameters studied were Body Weight (BW), BMI-for-Age z-Score (BAZ), Waist Circumference (WC), Waist-to-Hip Ratio (WHR), and Waist-to-Height Ratio (WHtR) and all were measured according to WHO procedure. Receiver Operating Characteristics (ROC) was used to analyze the potential of anthropometric parameter to predict anemia status. Based on multivariate analysis, a significant correlation was found between age (OR=0.88; 95% CI:0.79‒0.97) and WHtR (OR=0.12; 95% CI:0.02‒0.63) with anemia status. The ROC analysis revealed that the WHtR parameter had the highest Area Under the Curve (AUC) for predicting anemia, although with a very low accuracy (AUC=0.529). The optimal cut-off with value of WHtR for adolescent girls was ≤0.44. This study suggests that WHtR is a potential parameter for early detection of anemia status among adolescent girls and needs to be confirmed with further studies.